Motivations, expectations, and experiences of expatriate academic staff on an international branch campus in China - Cai, Li; Hall, Chris (Sage, 2016)
This article explores the experiences of non-Chinese academic staff working on an international branch campus in China. The article presents findings from an interview study that explored the expectations of expatriate staff and what motivated them to want to work abroad. The second part of the article reports on whether and how these expectations and motivations were fulfilled. The findings suggest that, although staff found many benefits from working on the international branch campus, they were insufficiently prepared for the structural and cultural differences inherent in working as an academic in China. The authors argue that more of the academics’ initial expectations and motivations could have been realized if better staff induction and ongoing collective professional development had been in place. In particular, university-level discourse communicated through policy and marketing texts, which promoted the vision of one inclusive and diverse international university community, militated against attention being paid to the structural, political, and cultural differences inherent in working as an academic in China. The authors argue that professional development that acknowledges the differences, difficulties, and disjunctions that staff are likely to encounter in their work is important in building successful international branch campuses both at the level of the organization and of the individual.